Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

I'm having some problems with the following assignment:

Let $X_1, X_2, ...,, X_n$ be samples from a exponential distribution with parameter $\lambda$, and let $c_1, c_2, ..., c_n$ be a sequence of positive numbers. Define \begin{align*} Y_i = \min(X_i, c_i) \quad \text{and} \quad \Delta_i = \textbf{1} \{ Y_i = X_i \}. \end{align*}

Determine the likelihood of the observed data $(Y_1, \Delta_1), (Y_2, \Delta_2), ....,(Y_n, \Delta_n)$.

My main problems are that I do not know how to calculate the pdf of the $Y_i$, and even if knowing those pdf's, I'm not sure how to use the $\Delta_i$ in the correct way.

What I've done so far:

I've first followed this post for calculating the pdf of $Y_i$: How to find the pdf of [min(RV.1,RV.2)]/RV.2

So, first notice that $Y_i$ is a random variable supported on $[ 0, c_i]$.

For $0 \leq y < c_i$ we see: \begin{align*} P(Y_i \leq y) = P(\min(X_i, c_i) \leq y) = P(X_i \leq y) = 1 - e^{-\lambda \; y} \end{align*}

For $y = c_i$ we see: \begin{align*} P(Y_i = y) = P(\min(X_i, c_i) = y) = P(X_i > y) = e^{- \lambda \; c_i} \end{align*}

Let $F_{Y_i}$ denote the distribution function of $Y_i$, then we see: \begin{align*} F_{Y_i}(y) &= 1 - e^{-\lambda \; y} &0 \leq y < c_i \\ F_{Y_i}(y) &= 1 &y = c_i \end{align*} and \begin{align*} f_{Y_i}(y) = \lambda e^{- \lambda y}, \quad 0 \leq y < c_i \end{align*} which obviously does not integrate to 1.

Disregarding that for the moment, it seems logical to me that the likelihoodfunction $\mathcal{L}(\lambda)$ then becomes \begin{align*} \mathcal{L}(\lambda) = \prod_{i = 1}^n \left( \Delta_i \lambda e^{- \lambda \; Y_i} + (1 - \Delta_i) e^{- \lambda \; c_i} \right). \end{align*}

Logging this statement we get \begin{align*} \log \mathcal{L}(\lambda) = \sum_{i = 1}^n \log\left( \Delta_i \lambda e^{- \lambda \; Y_i} + (1 - \Delta_i) e^{- \lambda \; c_i} \right) \end{align*} and calculating the derivative gives us \begin{align*} \frac{ \mathrm{d} \log \mathcal{L}(\lambda)}{ \mathrm{d} \lambda} = \sum_{i = 1}^n \frac{\Delta_i e^{\lambda \; c_i}( \lambda Y_i - 1) - c_i (\Delta_i - 1)e^{Y_i \; \lambda} }{(\Delta_i - 1)\lambda e^{\lambda \; Y_i} - \Delta_i \lambda e^{\lambda \; c_i}}. \end{align*}

But as far as I'm concerned, this brings us nowhere.

If someone could point out where I went wrong, I'd really appreciate it. Thanks in advance for any replies!

share|cite|improve this question
up vote 0 down vote accepted

The approach is correct. Contrary to the title of the question, the $c$'s are designated as constants. So $Y_i$ has the distribution of $X_i$ but with a ceiling, and each time we hit the ceiling, the probability is allocated to $c_i$. So the distribution function is indeed

$$\begin{align*} F_{Y_i}(y) &= 1 - e^{-\lambda y} &0 \leq y < c_i \\ F_{Y_i}(y) &= 1 &y = c_i \end{align*}$$

The density is likewise step-wise, i.e.

$$\begin{align*} f_{Y_i}(y) &= \lambda e^{-\lambda y} &0 \leq y < c_i \\ f_{Y_i}(y)=1-F_{Y_i}(y\mid y<c_i) &= e^{- \lambda y} &y = c_i \end{align*}$$

which "integrates to unity" alright since (skipping formalities)

$$\int_{S_{Y_i}}f_{Y_i}(y)dy = \int_0^{c_i}\lambda e^{-\lambda y}dy + e^{- \lambda c_i} = - e^{-\lambda y} \Big |_0^{c_i}+ e^{- \lambda c_i} = -e^{- \lambda c_i} +1 +e^{- \lambda c_i} =1$$

Note that the density is discontinuous, except if $\lambda =1$.

As long as the $X_i$'s are assumed independent, your joint likelihood function is correct (just make the $y$'s lower-case), and it is a standard case of a likelihood function "regulated" by an indicator function. Note that there may be a small conceptual hurdle: if we observe $y_i = c_i$, does this mean that $y_i = x_i$ or not? Since $X_i$ is continuous and the probability of it acquiring a specific value is zero, we treat the case $Y_i = c_i$ as implying that $Y_i \neq X_i$. Your indicator function is equivalent to $\Delta_i = \textbf{1} \{ y_i <c_i \}$, totally deterministic, given the sample.

If you want to proceed with estimation, you are presumed to know the $c$-constants (otherwise, you do not have enough data to estimate them). You also have a sample of $y_i$'s. Given these, you can create the indicator function series. Then the MLE for $\lambda$ will run as an iterative numerical estimation procedure. What, were you hopping to obtain an analytical solution?

To verify that your gradient is correct, assume that you obtain a sample of $y_i$'s in which $y_i<c_i,\; \forall i$. Then $\Delta_i =1,\; \forall i$ and the gradient becomes

$$ \frac{ \mathrm{d} \log \mathcal{L}(\lambda)}{ \mathrm{d} \lambda} = -\sum_{i = 1}^n \frac{( \lambda y_i - 1)}{\lambda } = 0 \Rightarrow \frac 1 {\lambda} = \frac 1n \sum_{i = 1}^n y_i $$

which is as it should, since, if all $y_i$ -realizations are below the ceiling, then the $Y_i$'s are treated as proper exponential variables themselves, and the ceilings, being non-binding, do not affect the estimation.

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.